South Korea and the Pitfalls of East Asian Monetary Regionalism: Do Neighbors Mean Neighborly Behavior?1. (April 2014) - Cho, Youngwon
<x xml:space="preserve">Abstract</x> In the aftermath of the Asian financial crisis, monetary regionalism has been widely advocated as a means to shelter East Asia from not only the volatility of global financial markets but also from the US‐dominated International Monetary Fund. While the primary obstacle to deepening regional monetary cooperation centered around the Chiang Mai Initiative (CMI) is cogently identified as being political, the existing literature focuses mostly on the rivalry between the likely lenders, China and Japan, and neglects the likely borrowers. Using the case of South Korea, this paper provides a cautionary tale of the CMI from a borrower's perspective. Any workable liquidity‐support arrangement, regional or otherwise, requires a robust surveillance mechanism to address the problem of moral hazard inherent to such a lending facility. In turn, an effective surveillance mechanism inevitably implies a significant political leverage for the lenders and vulnerability for the borrowers, an outcome that cannot be assumed to be avoidable by the CMI just by the virtue of its regional scope. There is little basis to expect that being neighbors necessarily means neighborly behavior; mere geographic proximity does not make China and Japan any less self‐interested than the United States, nor does it make Korea's potential political costs more tolerable.